Synthesis and thermoluminescence studies of UV-C exposed Li4Ca(BO3)2: Dy3+ phosphors. (October 2018) - Neharika,; Sharma, J.; Sharma, Vishal; Bedyal, A.K.; Swart, H.C.; Kumar, Vinay
Abstract: Thermoluminescence (TL) response of trivalent dysprosium ion doped Li4 Ca(BO3 )2 phosphor prepared by combustion method was studied. The samples were exposed to ultraviolet (UV-C) radiation (254 nm). The orthorhombic crystal structure of the Dy 3+ doped Li4 Ca(BO3 )2 nanophosphors was confirmed by X-Ray diffraction patterns. The TL glow curves showed a broad peak around 419 K with a shoulder around 482 K. The dose response curve of Dy 3+ doped Li4 Ca(BO3 )2 phosphor was studied by exposing the optimized sample for different exposure time ranging from 30 min to 5 h at the heating rate of 10 K/s. A shift of the peak towards higher temperature with an increase in dose indicates that the TL glow peak obeyed a non-first order kinetics. The TL intensity was also found to increase with increase in heating rate. The trapping parameters such as activation energy, order of kinetics were also calculated by using Chen's peak shape method. The optical and thermal fading of UV-C (254 nm) exposed Dy 3+ doped Li4 Ca(BO3 )2 have been studied. Experimental results suggest the Dy 3+ doped Li4 Ca(BO3 )2 as a good candidate to be employed as a complementary thermoluminescent devices. Highlights: First time, the TL study of Dy 3+ doped Li4 Ca(BO3 )2 phosphors exposed to UV-C radiations have been reported. Experimental results suggest a good candidate for complementary TL dosimetry.